Pengembangan Pemimpin Kristen: Kontribusi Motif Servant Leadership dan Keterampilan Intrapersonal - Waluwandja, Petrisia Anas; Dami, Zummy Anselmus; Selan, David Ranlyns E. (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
The study aimed to propose a combined final framework for the development of Christian leaders. The research method used is qualitative with a document analysis approach. There are seven important themes found in the study, including Christian formation, servant leadership motives, personal formations, relational skills, intellectual skills, intrapersonal skills, and management skills. This discovery is an extension of previous research that found only five important themes, namely Christian formation, personal formation, relational skills, intellectual skills, and management skills. This study resulted in two important themes that complement the weaknesses or shortcomings of previous research, namely the motive of servant leadership and intrapersonal skills. The motive of servant leadership consists of serving, influencing, and improving, while intrapersonal skills include humility, credibility, and authenticity.